2009
DOI: 10.4161/hv.9898
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of varicella vaccination in Swiss children and adolescents

Abstract: This study explores the effects of three different 2-dose varicella zoster virus (VZV) vaccination strategies in Switzerland. The EVITA model was used to assess clinical benefits and costs of strategies (1) vaccination of 11-15 year old adolescents with a negative or uncertain history for chickenpox, (2) universal vaccination of toddlers at age 1 to 2 years, and (3) strategy 2 plus catch-up vaccination of 11-15 year old susceptible adolescents. The cost-effectiveness analysis compares strategies 2 and 3 versus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…The review evidenced that the quality score of the studies varied over years, even in the same year and in analyses conducted by the same authors: Scuffham et al 22 vs. Scuffham et al 23 26,27,31,34,38,39,41,42,44 The results of Scuffham et al 22,23 varied in different environments: in 1999 they affirmed that the introduction of varicella program is cost saving for the New Zealand society, while in Australia, the childhood vaccine program is still preferred but has greater costs than the no vaccination program. Furthermore, according to Getsios et al, 28 the childhood vaccination program is not cost-effective for the Canadian healthcare system.…”
Section: Introductionmentioning
confidence: 95%
“…The review evidenced that the quality score of the studies varied over years, even in the same year and in analyses conducted by the same authors: Scuffham et al 22 vs. Scuffham et al 23 26,27,31,34,38,39,41,42,44 The results of Scuffham et al 22,23 varied in different environments: in 1999 they affirmed that the introduction of varicella program is cost saving for the New Zealand society, while in Australia, the childhood vaccine program is still preferred but has greater costs than the no vaccination program. Furthermore, according to Getsios et al, 28 the childhood vaccination program is not cost-effective for the Canadian healthcare system.…”
Section: Introductionmentioning
confidence: 95%
“…Alternatively, the addition of a second dose provides protection against all severities [25]. The economics of implementing one- or two-dose schedules have been widely debated [20,26,27], but national choices will ultimately depend on whether their priorities are varicella elimination or prevention of severe disease. Interestingly, a recent modeling study from Italy demonstrated that out of coverage, efficacy, number of doses, or dosing interval, high coverage is the critical success factor [28].…”
Section: Introductionmentioning
confidence: 99%
“…22 Not surprisingly, most cases occurred in young children who are known to be mainly affected by varicella and median age of patients (5 years) was the same as in a similar study from Germany. 21,23 It should be noted that this study was not population based but observational which means that the age distribution of our patients may not accurately reflect the occurrence of varicella in the general population. This may explain the relatively high proportion (76%) of cases in children up to 6 years of age in this study compared to seroprevalence rates and age distribution of hospitalized cases (with approximately 50% up to 6 years of age) obtained in previous studies in Switzerland by members of our group.…”
Section: Discussionmentioning
confidence: 95%